1987
DOI: 10.1021/om00147a030
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of phosphorus-bridged ferrocenophane Fe(.eta.5-C5H4PPh)(.eta.5-C5H4) with LiC5H5 and NaFe(CO)2(.eta.5-C5H5). Structures of {Fe[(.eta.5-C5H4)2]P(C6H5)-P}Fe(H)(.eta.5-C5H5)(CO) and {(C6H5)[Fe(.eta.5-C5H5)(.eta.5-C5H4)][Fe(.eta.5-C5H5)(.eta.5-C5H3C(O))]P-P,C}Fe(.eta.5-C5H5)(CO).cntdot.CHCl3

Abstract: No. [H2Et2][HFe3(CO)n], 2N][HFe3(CO)u], 107011-15-4; [H2(i-Pr)2N][HFe3(CO)n], 107011-16-5; [PPN][HFe3(CO)nJ, 23254-21-9; [HEt3N][HFe3-(CO)u], 56048-18-1; K[HFe3(CO)n], CO, Supplementary Material Available: Table IV, fractional coordinates (X104) for the hydrogen atoms of [H2(z-Pr)2][HFe3-(CO)u], and Table V, anisotropic temperature factors of [H2(t-Pr)2N][HFe3(CO)u] (2 pages); Table VI, observed and calculated structure factors (14 pages). Ordering information is given on any current masthead page.Reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 9 publications
1
6
0
1
Order By: Relevance
“…The dihedral angle, α, is 25.0°, which is comparable to the value of 26.9° for the free ligand FCPP 2a. It is thus confirmed that the strain of the [1]ferrocenophane unit is almost intact when FCPP coordinates to a metal, as previously described for [Cp(CO)HFe(FCPP)] ( 3 ), in which α is 25.4° give us an interesting structural feature of the phosphorus-bridged [1]ferrocenophane.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The dihedral angle, α, is 25.0°, which is comparable to the value of 26.9° for the free ligand FCPP 2a. It is thus confirmed that the strain of the [1]ferrocenophane unit is almost intact when FCPP coordinates to a metal, as previously described for [Cp(CO)HFe(FCPP)] ( 3 ), in which α is 25.4° give us an interesting structural feature of the phosphorus-bridged [1]ferrocenophane.…”
Section: Resultssupporting
confidence: 84%
“…Since the ferrocenophane has lone-pair electrons on the phosphorus, it may serve as a ligand toward a transition metal. Several complexes ( 1 − 4 ) 1b, possessing a phosphorus-bridged [1]ferrocenophane as a ligand have been synthesized. However, their reactivities have not yet been examined.…”
Section: Introductionmentioning
confidence: 99%
“…[110,111] High-molecular-weight material can also be obtained by thermal ROP and, as shown by Miyoshi and co-workers, by photoirradiation in THF. [105,112] Strained phospha [1]ferrocenophanes 29 can also coordinate through the lone pair on phosphorus to metal fragments (Scheme 4), [113][114][115][116][117] which alternatively may insert into a PÀC bond (Scheme 5). [118,119] Stable phosphonium-bridged [1]ferrocenophanes, sulfurized P V derivatives, and borane adducts of (phenyl)phospha[1]-ferrocenophanes (31) have been prepared and in some cases and subjected successfully to thermal transition-metal-catalyzed ROP.…”
Section: Ansa Complexesmentioning
confidence: 99%
“…Polymere mit hohem Molekulargewicht werden auch bei der thermischen ROP erhalten, und, wie Miyoshi und Mitarbeiter zeigten, auch durch Bestrahlen in THF 105. 112 Die gespannten Phospha[1]ferrocenophane 29 können über das freie Elektronenpaar des Phosphoratoms an weitere Metallfragmente koordinieren (Schema ),113117 die auch in die P‐C‐Bindung inserieren können (Schema ) 118. 119 Stabile phosphoniumverbrückte [1]Ferrocenophane, sulfurierte Phosphor(V)‐Derivate und Boranaddukte von Phenylphospha[1]ferrocenophanen ( 31 ) wurden hergestellt, und mit einigen gelang eine thermisch ausgelöste übergangsmetallkatalysierte ROP 120.…”
Section: Metallorganische Ringe Mit Zwei Cyclopentadienylliganden:unclassified